Dissemination of a successful dementia care program: Lessons from early adopters. Issue 9 (25th May 2022) - Lees Haggerty, Kristin; Campetti, Randi; Stoeckle, Rebecca Jackson; Epstein‐Lubow, Gary; Evertson, Leslie Chang; Spragens, Lynn; Serrano, Katherine Sy; Jennings, Lee A.; Reuben, David B.
Abstract: Background: Evidence‐based models for providing effective and comprehensive care for Alzheimer's disease and related dementias exist but have yet to be successfully implemented at scale. The Alzheimer's and Dementia Care Program (ADC Program) is an effective comprehensive dementia care model that is being disseminated across the United States. This qualitative study examines barriers and facilitators to implementing the model among early adopting sites. Methods: This study included semi‐structured interviews with a total of 21 clinical site leaders and Dementia Care Specialists from a total of 11 sites across the US. Interviews were audio recorded, transcribed, and coded using Dedoose qualitative analysis software. Coding scheme development and data interpretation were informed by Rogers' Diffusion of Innovations framework. Results: Key themes are organized in line with Rogers' framework. These include: the innovation‐decision process, implementation and characteristics of the innovation, and sustainability. Conclusions: Across the three overarching themes presented in this manuscript, the importance of engagement from site leaders, the multifaceted nature of the dementia care specialist role, and the value of technical assistance from qualified experts are apparent. However, for this work to continue to be successful, there needs to be more appropriate payment to cover needed services and a mechanism for supporting comprehensive dementia care over time. Abstract : See related article by Reuben et al . and Editorial by Callahan et al . in this issue.